Exploring Specific Physical Conditions as Determinants of Cataloguers’ Job Satisfaction in Federal and State Universities’ Libraries in South-South Zone of Nigeria - M. O., IG-Worlu; H. E., Chiekezie (International Journal of Social Service and Research, 2023)
This study explored specific physical conditions as determinants of cataloguers’ job satisfaction in federal and state universities’ libraries in South-South zone of Nigeria. The descriptive survey design was adopted for the study. Two objectives with its corresponding research questions and hypotheses guided the study. 109 cataloguers from 6 federal and 6 state universities libraries in the South-South zone of Nigeria made up the target population for the study. Stratified and total census sampling techniques were used to select the sample size of the study comprising 57 and 52 cataloguers from the federal and state universities’ libraries respectively. A self-structured, self-administered instrument entitled specific physical conditions for cataloguers job satisfaction questionnaire with a reliability coefficient of 0.82 was used for data collection. Descriptive and inferential statistics were used to answer the research questions and test the hypotheses respectively. Findings revealed that while workspace cleanliness met their expectations, both lighting and air quality standards were inadequate. Furthermore, these cataloguers highlighted that furniture comfortability and temperature settings also had a significant impact on job satisfaction. As such, it can be concluded that physical conditions within university libraries in South-South zone of Nigeria have a direct effect on the job satisfaction of cataloguers. Hence, it was recommended that periodic assessment of the universities’ libraries facilities should be carried out and resources must be allocated for infrastructure development to improve the existing physical conditions in the universities’ libraries.